A emancipação humana no pensamento filosófico de Walter Benjamin: Romantismo, Messianismo e Marxismo - Gonçalves, Jhonatan (2021)
This dissertation addresses the theme of understanding romanticism, Jewish messianism and Marxism to highlight a possible formulation of a theory of human emancipation in the philosophical thought of Walter Benjamin. Thus, the problem is to demonstrate Benjamin's articulation of Jena's first Romanticism – the object of reflection in his youth –, of theological messianism and, finally, of the method of historical and dialectical materialism, to then substantiate – which is evident in the writings of 1930 –, the specificity of his conception of criticism of capitalist modernity and of his proposal for a radical policy for the emancipation of the defeated. At first, it seeks to expose Benjamin's appropriation of the theory of knowledge of the first German romanticism to support his critique as well as his political-emancipatory perspective. The second moment intends to expose the affinities between Benjamin and the theology of heterodox Judaism, as well as his appropriation of Jewish messianism, highlighting how the categories of Judaism contributed to the later formation of his philosophy of history. Finally, the third moment exposes Benjamin's articulation of romanticism and Jewish messianic theology even after his assimilation of historical and dialectical materialism. Demonstrating, then, the defense of the hypothesis that Benjamin has continued certain elements of his occupation phase with German idealism and with the theological and messianic aspects of heterodox Judaism even after his inclination to Marxism. The work of the theses On the concept of history (1940) will be presented as the synthesis or even the articulation of problems apparently so distinct and contradictory among themselves that Benjamin seeks to establish for his critique of modernity and for his conception of human emancipation. The method used in this research will be an approach of Lucien Goldmann's genetic structuralism, carried out by Michael Löwy. The relevance of this method consists in analyzing the thought of an intellectual in question, based on the elective affinities between his theoretical production and other intellectuals in his historical context. It is understood that this research is relevant due to the need to think about Benjamin's conceptual constellation in light of contemporary problems. Furthermore, the effort to address the continuity of Benjamin's thought from his youth to maturity is pertinent due to the scarcity of studies that address the challenge of articulating messianism and Marxism.